2011
DOI: 10.1093/europace/eur360
|View full text |Cite
|
Sign up to set email alerts
|

Women and minorities are less likely to receive an implantable cardioverter defibrillator for primary prevention of sudden cardiac death

Abstract: Even after adjusting for comorbid conditions, gender, and racial discrepancies in the implantation of ICDs for the primary prevention of sudden cardiac death exist. Further investigations into the root causes of these discrepancies are needed before any corrective measures can be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
1
29
2
Order By: Relevance
“…Other studies have also shown that older patients 23,24 and women 25,26 are less likely to receive an ICD, with race also being a determinant. 27 In the present study, we did not observe any sex or race differences.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Other studies have also shown that older patients 23,24 and women 25,26 are less likely to receive an ICD, with race also being a determinant. 27 In the present study, we did not observe any sex or race differences.…”
Section: Discussioncontrasting
confidence: 51%
“…Other studies have also shown that older patients 23,24 and women 25,26 are less likely to receive an ICD, with race also being a determinant. 27 In the present study, we did not observe any sex or race differences.The presence of significant comorbidities in a subgroup (26%), especially neuropsychiatric comorbidities 23 and chronic dialysis, may have influenced the decision to implant a primary ICD, and most ICD trials have excluded patients with significant comorbidity. This could reflect provider judgment, patient preference, or possibly impairment of the patient's decision-making ability.…”
contrasting
confidence: 51%
“…Additional research has demonstrated that lifesaving therapies such as implantable cardioverter-defibrillators (ICDs) are underutilized in African Americans(9). While there has been an overall trend towards improved utilization of ICDs in all survivors of SCD (10), African American patients are still less likely than Caucasians to receive an ICD for primary prevention of SCA (11). …”
Section: Socioeconomic Factors and Racial Disparitiesmentioning
confidence: 99%
“…9-13 While these care differences appear to have lessened over time, they persist in contemporary practice. 14 It is unclear whether these differences result from a lack of empirical data on long-term effectiveness of ICDs in minority patients.…”
Section: Introductionmentioning
confidence: 99%